Impact of the natural hormonal milieu on ventral striatal responses to appetitive cigarette smoking cues: A prospective longitudinal study - Teresa R. Franklin; Nathaniel H. Spilka; Heather Keyser; Melanie Maron; Kanchana Jagannathan; Reagan R. Wetherill (Drug and Alcohol Dependence Reports, 2022)
Background: The female sex hormones estradiol (E) and progesterone (P) galvanize the ventral striatal reward pathway. E elevates ventral striatal dopamine and accelerates drug-cued reinstatement, while P has opposing ‘protective’ effects on drug-related behavior. We hypothesize that women may exhibit greater ventral striatal responses to smoking cues (SCs) during the late follicular phase of the menstrual cycle (MC) when E is high and unimpeded by P, and reduced responses during the late luteal phase when P is high. Methods: To test our hypothesis, 24 naturally cycling cigarette-dependent women completed functional magnetic resonance (fMRI) sessions over the course of 3 MCs at select time points to reflect the early follicular (low E and P; LEP, control condition), late follicular (high E, low P; HE) and mid-luteal (high E, high P; HEP) MC phases. During fMRI sessions (counterbalanced by phase), women were exposed to a SC versus nonSC audio-visual clip. Ovulation was verified for each MC, and hormone levels were acquired prior to sessions. Results: Contrasts within conditions showed that ventral striatal brain responses to SCs versus nonSCs were negligible during LEP and greater during HE (p=0.009) and HP (p=0.016). Contrasts across conditions showed that HE and HEP had greater responses than LEP (p=0.005), and HE had greater responses than HEP (p=0.049). Conclusions: Results support and extend our retrospective cross-sectional study of the influence of the hormonal milieu on SC reactivity. Results are clinically relevant as they may guide novel, hormonally-informed and immediately translatable treatment strategies that can potentially reduce relapse in naturally cycling women.